Building Madrasah Ibtidaiyyah Through Participation - M. Khusni Mubarok; Izzatul Fajriyah (JPDI (Jurnal Pendidikan Dasar Indonesia), 2017)
This research examines the public participation in establishing a madrasah Ibtidaiyyah held at MI Al-Hikmah Kalidawir. The methodology used was a qualitative approach. Data analysis procedures through three stages: data reduction, data presentation, and conclusion. There are three findings of the research, namely: first, the presence of some of the participating institutions in MI Al-Hikmah Kalidawir; secondly, the efforts of the madrasah and institutions to encourage people to participate in the school; and third, their work patterns and phases of the madrasah and institutions in realizing the ideals of schools that have superior quality and high participation. This research aims to determine the extent of public participation in the Madrasah Ibtidaiyyah.